2023
DOI: 10.1186/s12913-023-09072-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding integrated service delivery: a scoping review of models for noncommunicable disease and mental health interventions in low-and-middle income countries

Abstract: Background Noncommunicable diseases (NCDs) and mental health conditions represent a growing proportion of disease burden in low- and middle-income countries (LMICs). While past efforts have identified interventions to be delivered across health system levels to address this burden, the challenge remains of how to deliver heterogenous interventions in resource-constrained settings. One possible solution is the Integration of interventions within existing care delivery models. This study reviews … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Although a number of primary health care models of NCD care have been developed in sub-Saharan Africa, few have described an integrated, decentralized approach at the community level. A recent review of NCD and mental health interventions identi ed 188 studies of which only 29 were conducted in low-income countries [11]. Of these, just 11 were at the community or health centre level, and most focussed on a single disease or were small-scale pilot studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of primary health care models of NCD care have been developed in sub-Saharan Africa, few have described an integrated, decentralized approach at the community level. A recent review of NCD and mental health interventions identi ed 188 studies of which only 29 were conducted in low-income countries [11]. Of these, just 11 were at the community or health centre level, and most focussed on a single disease or were small-scale pilot studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent scoping review that summarised the characteristics of integrated care for NCDs and mental health in LMICs [ 45 ] also found that models of care were complex and heterogenous. Authors described the models of care according to pre-specified dimensions, of which the following mirror components that we identified: the condition, type of service, health care provider and health system level (where care was provided).…”
Section: Discussionmentioning
confidence: 99%
“…Patients seek hospitals capable of providing complete and thorough care, from diagnosis to follow-up and rehabilitation. Hospitals that can provide sustainable and coordinated services are more likely to be chosen by patients for service reuse because this creates comfort and trust in their treatment process (26).…”
Section: The Influence Of Service On Reuse Of Outpatient Servicesmentioning
confidence: 99%